Meningkatkan Hasil Belajar Siswa Kelas II pada Materi Matematika Perkalian Bilangan Cacah dengan Menggunakan Media Gambar di SDM PUU UPPO - Likka, Yusril Enga; Lede, Yulius Keremata; Making, Samuel Rex (Indo-MathEdu Intellectuals Journal, 2023)
The material of multiplication of whole number using picture media in class IIB SDM Puu Uppo. Type this research is classroom action research (PTK) which was carried out in two cycles with the steps of implementation planning, observation, and reflection. this research was carried out in class IIB odd semester with a total of 25 students. The resuts of the research shoul that using picture media can improve student learning outcomes in the whole number multiplication material in class IIB. There was an increase in learning outcomes from cycle I to cycle II and shouwed an increase and in the average value and percentage of complication in the classical cycle of 1,68 % with the number of students who completed 17 people and increase in the second cycle of classical completeness of 92 with the number of students who completed 23 students who had reachd 65 according to the specified minimum completion criteria (KKM) value. School the reculd of observation of frake activation from cycle I were 88 and increased in cycle II by 91. Resuld of observation of aktivities in cycle I were 82 and increased in cycle II by 94. Thus, the use of image media can improve student learning outcomes in the mathematical material of multiplication of number